Images Download Cite Share Favorites Permissions Review Article Assessment of prevalence of surgical site infections among diabetes patients in Nigeria hospitals - Olaolorunpo Olorunfemi; Oluwaseyi A Akpor; Kehinde S. Kolapo; Jeminat O Sodimu; Ngozi R. Osunde (Wolters Kluwer Medknow Publications, 2023)
Background and Aim Surgical site infections (SSIs) among diabetes patients are found to be the leading type of infection among hospitalized patients globally. Careful handling of surgical equipment reduces the chances of SSIs, and those who incorporate best practices can reduce the morbidity and mortality associated with SSIs. To assess the factors responsible for the high prevalence of SSIs among diabetes patients in Nigeria. Methods The data for this study were from published studies. Electronic databases of Medline, Scopus, PubMed, CINAHL, and Google Scholar were searched using the keywords: SSI, medical litigation, and literature were retrieved and screened for eligibility. The data limit considered in the literature search was from 2018 to 2022 to capture only the variables identified in this study objective. Results This study found that SSI among diabetes patients results from medical negligence or malpractice, which is a recurrent challenge in the field of medical practice in Nigeria. This occurs as a result of failure to carry out due diligence and professional responsibility in the acts or omissions of medical practitioners while discharging their duties in the treatment and care of their patients. Conclusion Nurses and other medical personnel must be aware that their practice could be a major trap for their litigation because most patients are becoming more aware of their rights, and the public will not forgive them when perceived harm to patients is as a result of medical negligence, or malpractice. There is a need to instill best practices that will reduce the morbidity and mortality associated with SSIs as a result of a breach of professional obligations.